KONSEP ADMINISTRASI DAN SUPERVISI PEMBELAJARAN - Nuraini Nuraini (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
Administration is often defined as the process of developing cooperative activities among a group of people to achieve predetermined goals, namely educational goals. Educational administration is a series or set of processes for controlling the cooperative efforts of a group of people to achieve educational goals in a planned and systematic manner within a specific environment, particularly formal educational institutions. Government Regulation No. 19 of 2005 concerning National Education Standards, Article 57, states that supervision, which includes managerial supervision and academic management supervision, is carried out regularly and continuously by supervisors or inspectors of educational units and heads of educational units. The National Education Standards Act explains that there are two types of supervision, namely managerial supervision and academic management supervision or academic supervision. The basic concepts of education administration and supervision explain the definitions of administration and supervision, the objectives and benefits of administration and supervision, the process of education supervision, and the approaches, techniques, and methods of education supervision. Learning supervision is a professional service that provides assistance, guidance, and simulation to teachers in order to improve the quality of their teaching and learning processes and their professionalism